Reactive Lymphoid Hyperplasia of the Pancreas: A Clinical Conundrum - Christophides, Thalis; Frampton, Adam Enver; Cohen, Patrizia; Gall, Tamara M H; Jiao, Long R; Habib, Nagy A; Pai, Madhava (JOP. Journal of the Pancreas, 2013)
Context Localized reactive lymphoid hyperplasia is a rare condition characterized by the presence of lymphoid follicles. Case report We describe a case of a 60-year-old woman who presented with right upper quadrant pain and was found to have a reactive nodular hyperplasia of the pancreas involving the uncinate process, body and tail of the gland. Due to the multifocal distribution of these hypoechoic vascular lesions, a total pancreatectomy was performed since malignancy could not be safely excluded. Conclusion There have been a handful of cases reporting reactive lymphoid hyperplasia affecting the pancreas; however, it is uncommon to perform such a radical pancreatic resection for this benign condition. Image: Several hyperplastic lymphoid follicles.